Analisis Tematik Kata Al-Insan (Manusia) yang Diiringi dengan Sifat-Sifat Tercela dalam Al-Qur’an - Abidin, Ahmad Zainal; Rofiah, Karinatur; Abidin, Alhadi Zaenal (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
The figure of a creature created by the Creator with glory and perfection inherent in him is the meaning of human beings. However, with this perfection, there are also shortcomings that accompany it, namely the despicable character in human identity. The aim of this research is to explain and explore related issues the despicable characteristics of humans through the word al-Insan which accompanied this characteristic along with its interpretation. With this, the author uses the thematic interpretation method in presenting explanations related to these characteristics, namely by referring to data, literature, reference sources through library research. The results of research into many despicable human traits in the Koran have been found, some of which include complaints, arrogance, love of material possessions, stubbornness, ungratefulness of favors, and forgetfulness of Allah. These characteristics arise because humans have followed their desires rather than their intellect, which ultimately leads to them falling into things that are prohibited by the Creator.